PERCEPÇÕES DOS PROFISSIONAIS DE SAÚDE DE NÍVEL SUPERIOR FRENTE AOS USUÁRIOS DE ÁLCOOL E OUTRAS DROGAS ATENDIDOS EM UMA UNIDADE DE SAÚDE DA FAMÍLIA (USF) EM CAMPO GRANDE – MS - Pamella Aline Miranda Teodoro (2023)
This study aims to identify the perceptions of higher-level health professionals regarding users of alcohol and other drugs treated at a USF in Campo Grande - MS, describe the barriers that hinder the bond and list the main strategies offered to users. The study was characterized as a qualitative, descriptive and exploratory study, where the sample consisted of 20 (twenty) higher-level health professionals working at the unit. the research was conducted by the researcher with professionals from eight different teams using a semi-structured interview script, the study population was formed by social workers, nurses, physiotherapists, doctors, dentists and physical education professionals. The results collected according to the metrics and compared with previous studies significantly point to increased consumption and dependence on alcohol and other drugs, and the interference of the effects on the individual's biopsychosocial aspect. The samples were predominantly female with a percentage of 75% (n=15), and only 25% (n=5) male. Age ranged from 25 to 46 years, with a mean value of 31.2 ± 6.52 years distributed between women and men. Of the 20 professionals, 95% are aware of users of alcohol and other drugs being treated in their unit, 100% are unaware of the existence of a care flow/planning for these cases. As for some type of qualification/training in the area of mental health/alcohol and drugs, about 35% (n=7) confirmed the accomplishment. Regarding the feeling of being able to assist and care for users of alcohol and other drugs treated at the USF, 40% (n=8) claimed yes, noting that many professionals claimed that this training is due to practice in the years of service and not the received knowledge. The result of this research correlates with studies already published, which the main challenge of health professionals are inadequate training, prejudice from professionals and users, lack of public and social policies and scarcity of resources. Descriptors: health promotion; drug users; primary health care.